Non-communicable diseases, an economic and health burden for the region (2002)
Looks at the measures which aim at diminishing the incidence of risk factors for chronic diseases, that, in many cases, are preventable with healthy habits or changes in eating behaviour.
Keywords: CHRONIC DISEASES